Driving MSMEs' Performance: The Impact of Social Media Adoption, Innovation Capability, and Government Support - Yordan Hermawan Apidana; Anton Prasetyo; Kholifah Kholifah; Dian Rusvinasari (Yayasan Riset dan Pengembangan Intelektual, 2024)
The purpose of this study is to investigates how social media adoption, innovation capability, and government support influence the business performance of micro, small, and medium enterprises (MSMEs) in Indonesia. Data were collected from 469 Indonesian MSME owners or managers via an online questionnaire and analyzed using structural equation models with the Partial Least Squares method. The results indicate that social media adoption positively impacts innovation capability and business performance. Additionally, innovation capability positively affects business performance and mediates the relationship between social media adoption and business performance. Moreover, government support acts as a moderator in the relationship between innovation capability and business performance. These findings provide practical insights for MSME owners or managers seeking to enhance their social media strategies and leverage innovation and government support to improve competitiveness in the digital market. The research also guides governments in formulating policies to boost MSMEs' business performance.